Effects of angiotensin converting enzyme inhibition on sodium excretion in patients with hypoxaemic chronic obstructive pulmonary disease. Issue 10 (October 1994) - Stewart, A G; Waterhouse, J C; Billings, C G; Baylis, P; Howard, P
Abstract : BACKGROUND--Some patients with hypoxaemic chronic obstructive pulmonary disease (COPD) develop cor pulmonale with sodium and water retention. The sodium retention has been explained as a result of increased plasma levels of aldosterone. If this was true angiotensin converting enzyme (ACE) inhibition would be expected to lower plasma levels of aldosterone and improve the renal excretion of sodium. METHODS--Six patients with stable hypoxaemic COPD (PaO2 < 8.0 kPa) and a history of an oedematous exacerbation received an intravenous hypertonic saline load (6 ml/kg body weight of 2.7% saline over one hour) before and while taking 4 mg/day perindopril, an ACE inhibitor, for one month. Aldosterone, antidiuretic hormone (ADH), plasma and urine electrolyte levels, osmolality, and volume were measured over four hours. The repeatability of the saline load test was assessed in six patients with a similar severity of hypoxaemic COPD. For comparison the saline load test was also performed in six patients with mild COPD. RESULTS--The hypertonic saline load test results were repeatable. Perindopril reduced the mean (SD) plasma level of aldosterone from 142 (88) pg/ml to 54 (24) pg/ml at 0 minutes before the saline infusion, and from 64 (35) pg/ml to 30 (17) pg/ml after the infusion without improving the urinary volume or sodium excretion. Before starting treatment with perindopril 43.7 (6.9) mmol (20%) of the sodium load was excreted compared with 49.6 (7.9) mmol (22% of load) when taking perindopril. Patients with mild COPD excreted more sodium (77.6 (21.4) mmol (38.7% of load)) despite having similar plasma aldosterone levels to those in the patients receiving perindopril. CONCLUSIONS--Patients with stable hypoxaemic COPD have an impaired ability to excrete sodium which is not improved by the administration of an ACE inhibitor. ACE inhibition lowered the plasma level of aldosterone without improving sodium excretion. This suggests that the inability of patients with hypoxaemic COPD to excrete sodium is not caused by their increased plasma levels of aldosterone.